2020
DOI: 10.5897/jeif2020.1043
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of social learning on the usage of formal financial services in Kampala, Uganda

Abstract: The use of formal financial services has been associated with increased financial wellbeing and overall economic growth. Efforts to increase financial inclusion have emphasized financial literacy provided through formal training and education without due recognition that people's financial behaviors and practices may be motivated by social interactions. The current study examines the moderating effects of social learning on the relationship between financial literacy and formal financial services usage within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Alshebami and Aldhyani (2022) study revealed that self-control played a negative role in the association between financial literacy and consumption of savings. Agabalinda and Isoh (2020) found that social learning moderates the relationship between financial literacy and financial service usage. Therefore, the current study is among the first to investigate the moderating effect of parental SES on the relationship between parental financial teaching and financial literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Alshebami and Aldhyani (2022) study revealed that self-control played a negative role in the association between financial literacy and consumption of savings. Agabalinda and Isoh (2020) found that social learning moderates the relationship between financial literacy and financial service usage. Therefore, the current study is among the first to investigate the moderating effect of parental SES on the relationship between parental financial teaching and financial literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Social, financial, and psychological factors influence the perception of adequate income for retirement (Herrador-Alcaide et al, 2021;Hershey et al, 2012) and there are significant differences in financial preparation for retirement between various socioeconomic and demographic profiles. There is no consensus on differences in financial preparation for retirement according to sex (Kumar et al, 2019;Noone et al, 2010) and age (Agabalinda & Isoh, 2020;Witvorapong et al, 2022). As for the variables marital status, dependents, educational level, income, race, and occupation (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Fatores sociais, financeiros e psicológicos influenciam a percepção da renda adequada à aposentadoria (Herrador-Alcaide et al, 2021;Hershey et al, 2012) e existem diferenças significativas de preparação financeira para aposentadoria entre diferentes perfis socioeconômicos e demográficos. Não existe um consenso sobre as diferenças de preparação financeira para aposentadoria segundo o sexo (Kumar et al, 2019;Noone et al, 2010) e a idade (Agabalinda & Isoh, 2020;Witvorapong et al, 2022). Já para as variáveis estado civil, dependentes, escolaridade, renda, raça e ocupação (cf.…”
Section: Introductionunclassified